2016
DOI: 10.1007/s11432-016-5577-x
|View full text |Cite
|
Sign up to set email alerts
|

Antenna selection for two-way full duplex massive MIMO networks with amplify-and-forward relay

Abstract: In this paper, the antenna selection problem is investigated for the relaying system with the base station having massive multiple antennas, where the relay station works in the full duplex mode and the two-way protocol. The antenna selection scheme is optimized by maximizing the minimum of the two signal to noise ratios (SNRs) with each corresponding to the uplink and the downlink traffics. With the optimized antenna selection scheme, the approximate probability density function (PDF) of the received SNR for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our recent prototyping system in large-scale distributed MIMO has demonstrated that the data rate of 10Gbps could be achieved by a 128x128 large-scale distributed MIMO (or CF massive MIMO) with 100MHz bandwidth [21]. Different from the existing works, in this paper, we propose a network-assisted full duplex (NAFD) to unify the flexible duplex, hybrid-duplex, full-duplex, and other duplex methods [7], [14], [15], [22] under the CF massive MIMO network, and solve the CLI problem to achieve truly flexible duplex, which is essential in the 5G NR [17] and 6G systems. To demonstrate the superiority of NAFD with CF massive MIMO, the performance comparisons between NAFD and the existing duplexing methods are worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent prototyping system in large-scale distributed MIMO has demonstrated that the data rate of 10Gbps could be achieved by a 128x128 large-scale distributed MIMO (or CF massive MIMO) with 100MHz bandwidth [21]. Different from the existing works, in this paper, we propose a network-assisted full duplex (NAFD) to unify the flexible duplex, hybrid-duplex, full-duplex, and other duplex methods [7], [14], [15], [22] under the CF massive MIMO network, and solve the CLI problem to achieve truly flexible duplex, which is essential in the 5G NR [17] and 6G systems. To demonstrate the superiority of NAFD with CF massive MIMO, the performance comparisons between NAFD and the existing duplexing methods are worth studying.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the spectral efficiency and reduce latency, the fifth generation new radio supports flexible duplex technology in both the paired and unpaired spectrum, i.e., it allows frequency division duplex on a paired spectrum and time division duplex (TDD) operation on an unpaired spectrum. With co-frequency co-time full duplex (CCFD), a wireless transceiver can simultaneously transmit and receive in the same frequency band, and thus, the spectral efficiency could be further doubled by effectively eliminating self-interference [2]- [6]. Therefore, CCFD is one of the techniques enabling the sixth generation.…”
Section: Introductionmentioning
confidence: 99%